Advancing superhydrophobic surfaces: From mechanism insights and design strategies to intelligent applications - Weifeng Chen; Zhiwei Huang; Ting Xiao; Lihua Jiang; Xinyu Tan; Yizhu Lei (APL Materials)
Recently, superhydrophobicity has emerged as a pivotal field, offering immense potential across a wide range of industries. Despite the rapid progress made, challenges remain in developing durable and responsive superhydrophobic surfaces. This comprehensive review begins by exploring the fundamental mechanisms underlying superhydrophobicity, drawing on both classical and contemporary theories for crafting robust design strategies. The discussion then shifts to innovative design approaches for creating lasting superhydrophobic surfaces, addressing the need for durability and resilience in practical applications. Highlighting the cutting edge, we delve into the realm of smart superhydrophobic surfaces that dynamically adjust to environmental stimuli, such as temperature, light, magnetism, pH levels, and electric fields. We present groundbreaking progress in their ability to respond intelligently to changing environmental cues. Finally, we offer a forward-looking perspective on future trends in this area, highlighting opportunities for growth and innovation. This review not only consolidates current knowledge but also aims to spark new ideas in the design and helps in intellectualization of superhydrophobic surfaces, underscoring the importance of this vital field.